Social anxiety and the quality of life among undergraduate students in UiTM Puncak Alam Campus / Roslinda Isa, Nur Amylia Mohd Norsabri and Nur Aziemah Mohd Zamri - Isa, Roslinda; Mohd Norsabri, Nur Amylia; Mohd Zamri, Nur Aziemah (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Social anxiety disorder is frequent in children and adolescents, strongly associated with other anxiety disorders, depression, and substance use disorders. Objective: To assess the level of social anxiety and the quality of life among students in UiTM Puncak Alam Campus. Method: A cross-sectional study was conducted among the students from UiTM Puncak Alam Campus, Selangor. A total of 416 respondents were recruited by using convenience sampling. Questionnaire was divided into 3 parts: Part A: seven questions on demographic data, Part B: 24 questions on Liebowitz Social Anxiety Scale (LSAS) and Part C: 26 questions on Quality of Life Questionnaire (WHOQOL-BREF). Results: From 416 respondents, 148 (35.6%) had mild level of social anxiety and 49 (11.8%) had severe social anxiety. The quality of life (QoL) for the environment domain had the highest mean (68.20±16.81), while psychological had the lowest mean (61.88±18.63) compared to other domains. There was statistically significance relationship between social anxiety and quality of life, p<0.001. Conclusion: Social anxiety can be affected by many factors throughout entire phase of life and quality of life (QoL) also can contributed to the social anxiety problems.